Qatar's sports science and elite training programme for world-class performance at Aspire Academy - New initiatives - Cable, T.; Earle, C. J. (Asian Conference on sport science. Sport science and elite training programme for world class performance. 25-26 October 2013. Hong Kong Sports Institute, Hong Kong, China, 2013)
The Aspire Academy in Qatar is committed to the development of young athletes in sports that include football, athletics, squash and table tennis. This paper provides an insight to the Long Term Athlete Development Models that are utilized to build elite athletes and players of the future. This paper provides an in-depth insight into the processes and models of talent identification, multi-skill sports development and specific performance development programmes that operate in the enhancement of junior athletes in Qatar. An emphasis of the paper is on the close coupling of the coaching process with the provision of a holistic and integrated sports science support package that is evidence-based and research informed. The phased approach to coaching and sports science monitoring and assessment strategies that exist to maximize training response will also be addressed.